Pigmented Variants of Basal Cell Carcinoma: A Case Series - Nikhat Sajjad; Shaik Shaheen; Suwaiba Zakir Hussain; Urwa Nabilah; Noora Rabia Rahman (European Medical Journal Dermatology)
Background: Basal cell carcinoma (BCC) is a type of skin cancer. It typically develops in areas exposed to the sun, such as the face, neck, and hands. BCC usually appears as a raised, pearly bump with a central depression, or as a flat, scaly reddish patch. There are several types of BCC, and when melanin is present in the lesion it is called pigmented BCC, which are the types the authors are reporting in this case series. Aim: The aim of this study is to create awareness regarding a long-standing lesion turning into malignancy and to also alert health professionals for identification of signs and symptoms of BCC and the need for an early diagnosis. Method: A prospective observational study was carried out on patients presenting with pigmented variants of BCC. Conclusion: These cases highlight the importance of thorough clinical examination and biopsies supported by histopathological analysis aiding in diagnosis.